Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Correction: Mid-twenty-first century climate change in the Central United States. Part II: Climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2026)

Correction: Sub-Saharan Northern African climate at the end of the twenty-first century: forcing factors and climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Role of mid-level circulation and moisture accumulation in generating Lake Victoria’s extreme storms - Edward K. Vizy; Kerry H. Cook; Patrick C. Andrews (Climate Dynamics, 2026)

Escalating heat and humidity in the Congo Basin region: projections and implications for human health and labor - Kerry H. Cook; Edward K. Vizy; Patrick C. Andrews (Climate Dynamics, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Seasonality of rainfall in the Lake Victoria Basin is controlled by the large-scale circulation - Kerry H. Cook; Patrick C. Andrews; Edward K. Vizy (Climate Dynamics, 2025)

Cloud-top brightness temperature inconsistent indicator of extreme surface rainfall in western and central equatorial Africa - Patrick C. Andrews; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Operational lessons learned from simulating an elimination response to a transboundary animal disease in wild animals - K. Chalkowski; K.M. Pepin; M.J. Lavelle; R.S. Miller; J. Fischer; V.R. Brown; M. Glow; B. Smith; S. Cook; K. Kohen; S. Sherburne; H. Smith; et al. (Preventive Veterinary Medicine, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Understanding extreme rainfall in the Sahel of Southwestern Mali - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Greenhouse gas-induced modification of intense storms over the west African sahel through thermodynamic and dynamic processes - Siyu Zhao; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

Understanding the regionality and diurnal cycles of precipitation in the Lake Victoria Basin during Boreal fall - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

Mesoscale convective systems in the Congo Basin: seasonality, regionality, and diurnal cycles - Patrick C. Andrews; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

How shrinkage of Lake Chad affects the local climate - Siyu Zhao; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Hydrodynamics of regional and seasonal variations in Congo Basin precipitation - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Distribution of extreme rainfall events and their environmental controls in the West African Sahel and Soudan - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Greenhouse-gas induced warming amplification over the Arabian Peninsula with implications for Ethiopian rainfall - Kerry H. Cook; Edward K. Vizy; Yang Liu; Weiran Liu (Climate Dynamics, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Delayed retreat of the summer monsoon over the Indochina Peninsula linked to surface warming trends - Yang Liu; Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2021)
The Indochina Peninsula (ICP) is dominated by a tropical monsoon climate, and changes of the prevailing winds here have a marked impact on moisture and aerosol transport. September to early October is within the monsoon retreat period that is preceded by a change in the zonal wind from westerly to easterly. Here, we show the long‐term change of the monsoon retreat date and its related climate factors. Climatologically, the zonal wind is primarily controlled by the meridional land–sea temperature gradient through the geostrophic balance. A simple physical model suggests that a 1 K increase in this gradient is associated with a zonal wind speed change of 2.17 m·s −1 , and this estimate is consistent with reanalyses. Over the most recent 40 years there has been a positive trend of 0.107 K·decade −1 in the gradient, and linear regression shows that the average rate of delay of the summer monsoon retreat date over the ICP associated with trend in land–sea contrast is 23.5 day·K −1 . The mixing ratio gradient also makes a contribution to the monsoon retreat but its significance is lower than the land–sea temperature contrast. The ICP is located in a transitional zone bounded by three sub‐regions of Asia‐Pacific monsoon system; the delayed ICP monsoon retreat is most consistent with changes of the East Asian‐Western North Pacific monsoon.

Opposite spatial variability of climate change‐induced surface temperature trends due to soil and atmospheric moisture in tropical/subtropical dry and wet land regions - Jaya Khanna; Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2020)
Regional responses to surface warming are strongly influenced by the availability of surface or atmospheric moisture. For example, differences in evapotranspiration, atmospheric temperature lapse rate and heat capacity due to the availability of water over oceans and its lack over land contribute to an observed land/ocean warming ratio that is greater than one. This study shows that mechanisms related to the distributions of soil or atmospheric moisture could result in variations in regional climate change over land in the tropics and subtropics. Using atmospheric reanalyses and observations for the satellite era (1979–2016) within ±30° latitude, the analysis shows that dry regions such as northern and southern Africa and south‐central Australia have a significant negative regional spatial correlation between time‐averaged soil moisture/evapotranspiration and surface temperature trends. In contrast, wet tropical regions such as Amazonia and the Congo Basin display a significant positive spatial correlation between these quantities. Spatial correlations suggest that a regional amplification of surface temperature trends in wet regions could be associated with a robust positive longwave radiative effect of high clouds which co‐occur with wet soils. This positive relationship is strongest during austral summer, dominated by the summer seasons in the Amazon and Congo basins. These differences in regional sensitivity to greenhouse gas warming can be consequential for regional climate change assessment, for both tropical forests, which could already be operating at their high temperature limit, and also for dry desert regions, which are already marginal for supporting life.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Seasonal asymmetry of equatorial East African rainfall projections: understanding differences between the response of the long rains and the short rains to increased greenhouse gases - Kerry H. Cook; Rory G. J. Fitzpatrick; Weiran Liu; Edward K. Vizy (Climate Dynamics, 2020)

Influence of Indian Ocean SST regionality on the East African short rains - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2020)

Interannual variability of East African rainfall: role of seasonal transitions of the low-level cross-equatorial flow - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2020)

Examining multidecadal trends in the surface heat balance over the tropical and subtropical oceans in atmospheric reanalyses - Kerry H. Cook; Edward K. Vizy (International Journal of Climatology, 2020)
Trends in the components of the annual‐mean surface heat balance for 1979–2018 over the tropical and subtropical oceans are examined in multiple atmospheric reanalyses to understand how they are changing with current sea surface temperature (SST) trends. Confidence in the reanalysis values is evaluated through statistical significance, agreement among datasets, and physical analysis. While the climatology of the net surface heat flux is similar in the three reanalyses examined (ERAI, JRA‐55, and NCEP2), net heat flux trends agree only in the two second‐generation reanalyses. Trends in the 10‐m winds, which are assimilated in JRA‐55 and ERAI but not in NCEP2, are largely responsible for the disagreement. To first order, trends in the latent heat flux explain trends in the net surface heat flux over the tropical oceans. Trends in sensible heat are smaller, and trends in the net radiative components are relevant only regionally. The latent heat flux is decomposed into thermally, dynamically, and hydrologically driven components. Trends in the thermal component of the latent heat flux simply dampen SST trends through the Clausius–Clapeyron relationship. Dynamically driven trends are associated with an intensification of the tropical easterly trade winds, primarily of the equator and with greater enhancement in the Southern Hemisphere. They are generally supported by hydrologically driven trends, which are similar in magnitude to the wind‐driven trends.

Role of the West African westerly jet in the seasonal and diurnal cycles of precipitation over West Africa - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2020)

Congo Basin drying associated with poleward shifts of the African thermal lows - Kerry H. Cook; Yang Liu; Edward K. Vizy (Climate Dynamics, 2020)

Observed relationship between the Turkana low-level jet and boreal summer convection - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

Changes in intense rainfall events and dry periods across Africa in the twenty-first century - Fan Han; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2019)

Contemporary Climate Change of the African Monsoon Systems - Kerry H. Cook; Edward K. Vizy (Current Climate Change Reports, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Understanding the summertime diurnal cycle of precipitation over sub-Saharan West Africa: regions with daytime rainfall peaks in the absence of significant topographic features - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

The role of mesoscale convective systems in the diurnal cycle of rainfall and its seasonality over sub-Saharan Northern Africa - Weiran Liu; Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2019)

Land–atmosphere–ocean interactions in the southeastern Atlantic: interannual variability - Xiaoming Sun; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2019)

Decadal change of the south Atlantic ocean Angola–Benguela frontal zone since 1980 - Edward K. Vizy; Kerry H. Cook; Xiaoming Sun (Climate Dynamics, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Multidecadal-scale adjustment of the ocean mixed layer heat budget in the tropics: examining ocean reanalyses - Kerry H. Cook; Edward K. Vizy; Xiaoming Sun (Climate Dynamics, 2018)

Mesoscale convective systems and nocturnal rainfall over the West African Sahel: role of the Inter-tropical front - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2018)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia - N. L. Parchem; K. A. Bauer; C. H. Cook; J. E. Mangino; C. D. Jones; K. Porter; C. V. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The Congo Basin Walker circulation: dynamics and connections to precipitation - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Understanding long-term (1982–2013) multi-decadal change in the equatorial and subtropical South Atlantic climate - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2016)

Projected changes in Malawi’s growing season - Edward K. Vizy; Kerry H. Cook; James Chimphamba; Brent McCusker (Climate Dynamics, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Reconstruction of the springtime East Asian Subtropical Jet and Western Pacific pattern from a millennial-length Taiwanese tree-ring chronology - W. E. Wright; B. T. Guan; Y.-H. Tseng; E. R. Cook; K.-Y. Wei; S.-T. Chang (Climate Dynamics, 2015)

The relationship between African easterly waves and daily rainfall over West Africa: observations and regional climate simulations - Julien Crétat; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2015)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Reduction of circulating and selective limbic brain levels of (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP) following forced swim stress in C57BL/6J mice - Antoniette M. Maldonado-Devincci; Matthew C. Beattie; Danielle H. Morrow; Raechel E. McKinley; Jason B. Cook; Todd K. O’Buckley; A. Leslie Morrow (Psychopharmacology, 2014)

Impact of cold air surges on rainfall variability in the Sahel and wet African tropics: a multi-scale analysis - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Identifying hot spots of security vulnerability associated with climate change in Africa - Joshua W. Busby; Kerry H. Cook; Edward K. Vizy; Todd G. Smith; Mesfin Bekalo (Climatic Change, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

How well are daily intense rainfall events captured by current climate models over Africa? - Julien Crétat; Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Capturing the Atlantic cold tongue and coastal upwelling in an intermediate-level ocean model coupled to a regional climate model - Edward K. Vizy; Kerry H. Cook (Climate Dynamics, 2014)

Mid-twenty-first century climate change in the Central United States. Part II: Climate change processes - C. M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2013)
Ensemble regional model simulations over the central US with 30-km resolution are analyzed to investigate the physical processes of projected precipitation changes in the mid-twenty-first century under greenhouse gas forcing. An atmospheric moisture balance is constructed, and changes in the diurnal cycle are evaluated. Wetter conditions over the central US in April and May occur most strongly in the afternoon and evening, supported primarily by moisture convergence by transient eddy activity, indicating enhanced daytime convection. In June, increased rainfall over the northern Great Plains is strongest from 0000 to 0600 LT. It is supported by positive changes in stationary meridional moisture convergence related to a strengthening of the GPLLJ accompanied by an intensification of the western extension of the North Atlantic subtropical high. In the Midwest, decreased rainfall is strongest at 1500 LT and 0000 LT. Both a suppression of daytime convection as well as changes in the zonal flow in the GPLLJ exit region are important. Future drying over the northern Great Plains in summer is triggered by weakened daytime convection, and persists throughout August and September when a deficit in soil moisture develops and land–atmosphere feedbacks become increasingly important.

Impact of climate change on mid-twenty-first century growing seasons in Africa - Kerry H. Cook; Edward K. Vizy (Climate Dynamics, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Sub-Saharan Northern African climate at the end of the twenty-first century: forcing factors and climate change processes - Christina M. Patricola-DiRosario; K. H. Cook (Climate Dynamics, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Soil Carbon Characteristics in Two Mississippi River Deltaic Marshland Profiles - Jim J. Wang; Syam K. Dodla; Ronald D. DeLaune; Wayne H. Hudnall; Robert L. Cook (Wetlands, 2011)

Negative feedback in the cold: ice retreat produces new carbon sinks in Antarctica - L. S. PECK; D. K. A. BARNES; A. J. COOK; A. H. FLEMING; A. CLARKE (Global Change Biology, 2010)
Feedbacks on climate change so far identified are predominantly positive, enhancing the rate of change. Loss of sea‐ice, increase in desert areas, water vapour increase, loss of tropical rain forest and the restriction of significant areas of marine productivity to higher latitude (thus smaller geographical zones) all lead to an enhancement of the rate of change. The other major feedback identified, changes in cloud radiation, will produce either a positive feedback, if high level clouds are produced, or a negative feedback if low level clouds are produced. Few significant negative feedbacks have been identified, let alone quantified. Here, we show that the loss of ice shelves and retreat of coastal glaciers around the Antarctic Peninsula in the last 50 years has exposed at least 2.4 × 10 4 km 2 of new open water. We estimate that these new areas of open water have allowed new phytoplankton blooms containing a total standing stock of ∼5.0 × 10 5 tonnes of carbon to be produced. New marine zooplankton and seabed communities have also been produced, which we estimate contain ∼4.1 × 10 5 tonnes of carbon. This previously unquantified carbon sink acts as a negative feedback to climate change. New annual productivity, as opposed to standing stock, amounts to 3.5 × 10 6 tonnes yr −1 of carbon, of which 6.9 × 10 5 tonnes yr −1 deposits to the seabed. By comparison the total aboveground biomasses of lowland American tropical rainforest is 160–435 tonnes ha −1 . Around 50% of this is carbon. On this basis the carbon held in new biomass described here is roughly equivalent to 6000–17 000 ha of tropical rainforest. As ice loss increases in polar regions this feedback will become stronger, and eventually, over thousands to hundreds of thousands of years, over 50 Mtonnes of new carbon could be fixed annually in new coastal phytoplankton blooms and over 10 Mtonnes yr −1 locked in biological standing stock around Antarctica.

The WAMME regional model intercomparison study - Leonard M. Druyan; Jinming Feng; Kerry H. Cook; Yongkang Xue; Matthew Fulakeza; Samson M. Hagos; Abdourahamane Konaré; Wilfran Moufouma-Okia; David P. Rowell; Edward K. Vizy; Seidou Sanda Ibrah (Climate Dynamics, 2010)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Inducible transcription of genes involved in taurine uptake and dissimilation by Silicibacter pomeroyi DSS-3T - Andzelika K. Gorzynska; Karin Denger; Alasdair M. Cook; Theo H. M. Smits (Archives of Microbiology, 2006)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Growth comparisons of avian infectious bronchitis virus strains in organ cultures of chicken tissues - J. H. Darbyshire; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1978)

The use of chicken tracheal organ cultures for the isolation and assay of avian infectious bronchitis virus - Jane K. A. Cook; J. H. Darbyshire; R. W. Peters (Archives of Virology, 1976)